Barriers and facilitators to physical activity participation for children with physical disability: comparing and contrasting the views of children, young people, and their clinicians. Issue 13 (19th June 2019) - Wright, Annemarie; Roberts, Rachel; Bowman, Grace; Crettenden, Angela
Abstract: Purpose: Existing research has explored the barriers and facilitators of physical activity participation for young people with disability from the perspective of young people and their families. However, little research has investigated the views of clinicians who facilitate access to physical activity programs and compared this with their child client's perspectives. Method: Interviews were conducted with six allied health and sports development professionals associated with a programme which supports access to recreation and sporting activities. Interviews explored facilitators and barriers to physical activity experienced by their clients. Open-ended survey questions investigating barriers and facilitators of physical activity participation were also completed by 28 young people with disability aged 10–17 years who were clients of this programme. Results: The most salient facilitator of participation described by clinicians was " planning programs to promote success and inclusion." Young people described two main facilitators; " the right people make physical activity fun !" and, similar to clinicians, " appropriate and inclusive opportunities to be active." The most salient barriers identified by clinicians were " practical limitations" and " time constraints and priorities, " and a novel barrier raised was " whose choice?" The "lack of accessible and inclusive opportunities" was the most pertinent barrier for young people. Conclusions: Clinicians should determine both parent and young person commitment to a physical activity before enrolment. Lack of commitment can act as a barrier to physical activity and a more appropriate intervention could focus on increasing awareness of the benefits of being active, drawing on a Stages of Change based model of service delivery. Implications for rehabilitation: Rehabilitation professionals seeking to increase physical activity participation for young people with physical disability should discuss readiness and motivation to change prior to any activity/sports referral. Different behaviour change processes are required for young people and for their parents and both are important to achieve physical activity participation. Regular monitoring is important to identify on-going physical and psychological barriers to participation, even for those who were already active. Clinicians should be aware that teenagers may be more ready to be active as they develop greater independence and should raise awareness of the benefits of physical activity.